Situations et savoirs dans la pratique de classe - Bernard Rey (Nantes Université, 2011)
According to a widespread idea, pupils learn by encountering situations. How do we have to consider the concept of situation to support such an idea? Is it possible that knowledge arises from situations? This text analyzes the difficulties that this theory entails. It tries to reveal the links between the notion of situation and those of competence and knowledge. It leads to an important distinction between context and situation.